Diseño de un modelo de gestión administrativa para el desarrollo del turismo comunitario en la comunidad Kichwa “Sinchi Pura” – Parroquia Talag - Cantón Tena-Provincia Napo. - Balseca Beltrán, Carla Elizabeth (2014)
Ecuador has seen tourism as a great opportunity to generate significant revenue and help with its economy, offering diverse forms of tourism among these we have the communitarian Tourism.